The Effect of Operational Audit, Internal Control, Implementation of Marketing Strategy and Sales Accounting Information System on Sales Effectiveness - Rachman, Purie Ayu Istiningdyah; Fitri, Hadiati (Research of Accounting and Governance, 2023)
The purpose of this study is to see if operational auditing, internal control, marketing strategy implementation, and sales accounting information systems have an impact on sales effectiveness. The research method employed in this study is quantitative. The data was collected using questionnaires, and the analysis method used was multiple linear regression. According to the findings of the study, operational auditing and accounting information systems have a significant impact on sales effectiveness. Internal control has no effect on the effectiveness of sales. Furthermore, the implementation of marketing strategies has an impact on sales effectiveness, but not significantly.